Diagenetic significance of carbon, oxygen and strontium isotopic compositions in the Aptian-Albian Mural Formation in Cerro Pimas area, northern Sonora, Mexico. - Madhavaraju, J.; IL Lee, Yong; González–León, C.M. (Journal of Iberian Geology, 2013)
A carbon, oxygen and strontium isotopic study on the predominantly carbonate succession of the shallow marine Mural Formation in the Cerro Pimas locality of northern Sonora (Mexico) was undertaken to understand isotopic variations in seawater during Aptian- Albian time. Petrographic study has been carried out on these limestones to support the isotopic study. The limestones show low content of TOC, both negative and positive δ13C values (-4.1 to +2.2‰ VPDB) and d18O values varying from -13.4 to -8.9‰ VPDB. The carbon isotope composition, δ13C vs δ18O plot and Mn/Sr ratio suggest that the δ13C measured values are primary in nature and remain unaltered during diagenesis. The carbon isotope curve shows a positive δ13C excursion followed by a negative event in the lower part of the Los Coyotes Member (Lower Albian) of the Mural Formation and confirm the global nature of the episode OAE 1b in the Cerro Pimas section. The 87Sr/86Sr ratios for limestones of the Mural Formation (0.707221 to 0.707340) are similar to the ratios for Late Aptian and Early Albian seawater (0.70726 to 0.70740). In addition, 87Sr/86Sr age of the Cerro La Ceja member (113.4 Ma; Late Aptian age) is comparable to that of published zircon radiometric age. The numerical age of Los Coyotes (112.0 Ma and 111.1 Ma) and Cerro La Espina (110.9 Ma and 110.7 Ma) members indicate also Early Albian age. The whole-rock Sr isotope ages in this study are consistent with the previously published radiometric and biostratigraphic ages.